2011
DOI: 10.1158/1078-0432.ccr-11-1424
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancers with Microsatellite Instability Display Unique miRNA Profiles

Abstract: Purpose microRNAs (miRNAs) are small non-coding transcripts that play an important role in carcinogenesis. miRNA expression profiles have been shown to discriminate between different types of cancers. The aim of this study was to analyze the global miRNA signatures in various groups of colorectal cancers (CRCs) based on the presence of microsatellite instability (MSI). Experimental Design We analyzed genome-wide miRNA expression profiles in 54 CRCs (22 with Lynch syndrome, 13 sporadic MSI due to MLH1 methyla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 37 publications
(51 reference statements)
3
80
0
Order By: Relevance
“…In addition, more than one-third of all CRC-associated mortalities (29% in men and 43% in women) occurred in individuals aged ≥80 years (1). Lynch syndrome (LS), previously termed hereditary non-polyposis colorectal cancer (HNPCC), accounts for 3% of all CRCs and is caused by a germline mutation in one of the mismatch repair (MMR) genes mutL homolog 1 (MLH1), mutS homolog (MSH) 2, MSH6 and PMS1 homolog 2, mismatch repair system component (PMS2), and LS is the most common hereditary form of CRC (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, more than one-third of all CRC-associated mortalities (29% in men and 43% in women) occurred in individuals aged ≥80 years (1). Lynch syndrome (LS), previously termed hereditary non-polyposis colorectal cancer (HNPCC), accounts for 3% of all CRCs and is caused by a germline mutation in one of the mismatch repair (MMR) genes mutL homolog 1 (MLH1), mutS homolog (MSH) 2, MSH6 and PMS1 homolog 2, mismatch repair system component (PMS2), and LS is the most common hereditary form of CRC (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs have also been found to be differentially expressed in microsatellite stable (MSS) groups compared to microsatellite instable (MSI) in addition to subgroups (MSI-high and low) in CRC [161,207]. As stated earlier, MSI tumors have a favorable prognosis compared to MSS tumors and the identification of these patients might influence treatment decisions.…”
Section: E) Mirna As Prognostic Biomarkersmentioning
confidence: 84%
“…Examining the top five highly expressed miRNAs for association with clinicopathological parameters revealed that reduced expression of miR-192-5p was associated with increased pT stage and poorly differentiated tumors. Reduced expression of miR-192 has previously been associated with MSI status in CRC while overexpression of miR-192 exhibited reduced cell proliferation by targeting cell cycle progression [207,208,253,254]. 71 The expression patterns represented by hierarchical clustering reveal that the miRNAs were relatively uniformly expressed across all the patient samples thereby supporting the lack of associations between miRNA expression and clinicopathological parameters or outcome.…”
mentioning
confidence: 88%
“…Valeri et al [46] demonstrated the association of reduced expression of MSH2, MLH1 and MSH6 and induction of a mutator phenotype and MSI with over expression of miR-155 in LS. In another study, Balaguer et al [47] determined the up-regulation of miR-622 and miR-1238 in these patients. MSI status modulates the miRNA expression levels [48] .…”
Section: Lsmentioning
confidence: 96%